From retribution to public safety: disruptive innovation of American criminal justice - Kelly, William R. (Rowman & Littlefield, 2017)
Acknowledgments -- Introduction -- The great American punishment experiment -- Four major threats to recidivism reduction: intellectual deficiencies, drug addiction, neurodevelopmental problems, and mental illness -- The special case of the juvenile brain -- The path forward: changing behavioral health -- Criminal intent and diversion -- The path forward: diverting disordered offenders -- Costs, benefits and challenges -- Notes -- References -- Index